2000
DOI: 10.2500/108854100778248269
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Skin Testing for Penicillin Allergy in an Inpatient Population: Analysis of the Subsequent Patient Management

Abstract: It was decided to assess the value of skin testing in a group of inpatients with a remote history of penicillin allergy, in terms of whether or not beta-lactams were subsequently given, if any adverse reactions occurred as a result of this therapy, and if labeling of the patient record was changed subsequent to skin testing and/or challenge. All patients seen in consultation with a history of penicillin allergy were assessed. When done, skin tests were performed with the major and minor determinants of penicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 2 publications
2
18
0
1
Order By: Relevance
“…In our study we found poor documentation of the results. Similar findings were reported by Warrington et al [22] in a study in which 49% of patients were still labeled as penicillin allergic despite having negative skin tests or an uneventful drug challenge. Poor documentation could be expected to be associated with discrepancies between the medical record and the allergy history [7].…”
Section: Discussionsupporting
confidence: 89%
“…In our study we found poor documentation of the results. Similar findings were reported by Warrington et al [22] in a study in which 49% of patients were still labeled as penicillin allergic despite having negative skin tests or an uneventful drug challenge. Poor documentation could be expected to be associated with discrepancies between the medical record and the allergy history [7].…”
Section: Discussionsupporting
confidence: 89%
“…The negative predictive value of inpatient allergy testing is comparable to outpatient and perioperative cohort data . Furthermore, the intervention has consistently shown to reduce the use of broad‐spectrum antibiotics, a finding that has been reported from studies in the perioperative setting . Antibiotic prescription changes in the inpatient setting may have greater implications than in the perioperative setting.…”
Section: Discussionmentioning
confidence: 63%
“…19,47 Furthermore, the intervention has consistently shown to reduce the use of broadspectrum antibiotics, a finding that has been reported from studies in the perioperative setting. 48 Antibiotic prescription changes in the inpatient setting may have greater implications than in the perioperative setting. Most inpatients receive antibiotics with therapeutic intent rather than prophylaxis with longer treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative antibiotics were still chosen for 43% of patients for whom beta-lactam therapy was recommended, and 50% of patients were mislabeled with penicillin allergy at discharge. 4 Prematta et al surveyed primary care physicians (internal medicine, pediatrics, family medicine, and internal medicine-pediatrics trained providers were included), and they found that there was great confusion regarding penicillin testing and the cross-reactivity and safety of utilizing other beta-lactams in the patient with penicillin allergy. 5 With the increase in the use of electronic medical records, one would assume that penicillin allergy labels would be more likely to be removed after documented tolerance or negative testing, but Rimawi et al found otherwise.…”
Section: To the Editormentioning
confidence: 98%